2014
DOI: 10.1007/s00429-014-0861-2
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral cerebello-thalamo-cortical pathways with prominent involvement of associative areas in humans in vivo

Abstract: In addition to motor functions, it has become clear that in humans the cerebellum plays a significant role in cognition too, through connections with associative areas in the cerebral cortex. Classical anatomy indicates that neo-cerebellar regions are connected with the contralateral cerebral cortex through the dentate nucleus, superior cerebellar peduncle, red nucleus and ventrolateral anterior nucleus of the thalamus. The anatomical existence of these connections has been demonstrated using virus retrograde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
163
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(179 citation statements)
references
References 95 publications
(179 reference statements)
14
163
1
1
Order By: Relevance
“…Cerebellar and cerebral areas co-activate during the performance of a wide range of cognitive tasks (Balsters et al, 2014;Stoodley and Schmahmann, 2009) and several studies using resting state functional magnetic resonance imaging (fMRI) report functional connectivity between the cerebellum and cerebral networks involved in both cognitive functions and motor control (Bernard et al, 2014;Buckner et al, 2011;Habas et al, 2009;Krienen and Buckner, 2009;O'Reilly et al, 2010;Ramnani, 2006;Sang et al, 2012). In line with these observations, diffusion tensor imaging (DTI) based tractography has provided evidence for white-matter tracts between the dentate nucleus -a major source of cerebellar output -and prefrontal and parietal areas (Jissendi et al, 2008;Palesi et al, 2014;Ramnani, 2006), suggesting extensive structural connections between the cerebellum and the associative cerebral cortex in humans.…”
Section: Introductionmentioning
confidence: 85%
“…Cerebellar and cerebral areas co-activate during the performance of a wide range of cognitive tasks (Balsters et al, 2014;Stoodley and Schmahmann, 2009) and several studies using resting state functional magnetic resonance imaging (fMRI) report functional connectivity between the cerebellum and cerebral networks involved in both cognitive functions and motor control (Bernard et al, 2014;Buckner et al, 2011;Habas et al, 2009;Krienen and Buckner, 2009;O'Reilly et al, 2010;Ramnani, 2006;Sang et al, 2012). In line with these observations, diffusion tensor imaging (DTI) based tractography has provided evidence for white-matter tracts between the dentate nucleus -a major source of cerebellar output -and prefrontal and parietal areas (Jissendi et al, 2008;Palesi et al, 2014;Ramnani, 2006), suggesting extensive structural connections between the cerebellum and the associative cerebral cortex in humans.…”
Section: Introductionmentioning
confidence: 85%
“…without SIFT or without any of the length-scaled related variants) therefore still has an important role to play, not as a quantitative map, but rather as a high-contrast anatomical image, particularly when used with super-resolution. This quality was in fact exploited in a number of recent TDI studies, including studies in ex vivo mouse brain (Calamante et al, 2012a;Kurniawan et al, 2014;Richards et al, 2014), ex vivo zebrafish brain (Ullmann et al, 2015), and in vivo human brain (Cho et al, 2015;Palesi et al, 2014). These studies demonstrate that there is still an important role for the high contrast standard TDI maps, regardless of this contrast originating in part from tractography biases.…”
Section: Quantitation Vs Image Contrastmentioning
confidence: 99%
“…2 Several studies have shown that advanced fiber tractography algorithms provide invaluable qualitative and quantitative information on the brain WM microstructure that cannot be obtained with conventional structural neuroimaging sequences. 2,4 Developments in high-angular-resolution diffusion imaging 5,6 and progress in postprocessing software that take into ac-count multiple fiber orientations in the same voxel have improved the correct anatomic reconstruction of WM tracts such as the afferent and efferent cerebellar pathways [5][6][7][8][9] by accommodating crossing fibers. Improvements in fiber tractography of the cerebellar pathways are important because a large number of congenital, acquired, or degenerative diseases of pediatric [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and adult 27-31 populations affect the cerebellum.…”
mentioning
confidence: 99%